Rekomendasai Tenaga Pengajar Pada Sekolah TK Nasional Plus Dengan Menggunakan Metode Simple Additive Weighting (SAW) - Dini Erlita; Lis Utari (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
In accepting teachers, each school will offer various criteria for prospective teachers. The process of accepting teachers at the Kinderfield Cibinong School is still done manually, where a file selection and comparison with existing criteria will be carried out. Based on the 8 (eight) criteria obtained from interviews with the principal, the weight value of each criterion is also obtained. The application of the method Simple Additive Weighting (SAW) to this problem is one of the most appropriate and effective ways. The existence of a system for the recommendation of teaching staff in national kindergarten schools plus will be more effective and efficient in its use. For the implementation of the system, the compiler uses the vb.net programming language and SQL Server as the database. With the Decision Support System, it can help in determining which prospective teachers will be accepted and the process will be faster